MATLAB Programming for Biomedical Engineers and Scientists - King, Andrew P., author 649073; Aljabar, Paul, author 649875; ScienceDirect (Online service) 7722 (London, United Kingdom : Academic Press is an imprint of Elsevier, 2017)
MATLAB Programming for Biomedical Engineers and Scientists provides an easy-to-learn introduction to the fundamentals of computer programming in MATLAB. This book explains the principles of good programming practice, while demonstrating how to write efficient and robust code that analyzes and visualizes biomedical data. Aimed at the biomedical engineer, biomedical scientist, and medical researcher with little or no computer programming experience, it is an excellent resource for learning the principles and practice of computer programming using MATLAB.